MALACOFUANA DIVERSITY OF RIVER CHENAB FED STREAM (GHO-MANHASAN) - K. K. SHARMA,; SAMITA CHOWDHARY,; ARTI SHARMA, (The Bioscan, 2011)
The paper deals with the study of Molluscan fauna diversity of a sub-tropical stream in J and K. Although molluscs are common components of the benthic communities, their role in the dynamics of the aquatic ecosystem and their contribution to biomass production is not well known. The overall diversity in the stream constitutes nine species. Among nine species seven species belongs to families Viviparidae, Thiaridae, Lymnoidae, Physidae and Planorbidae of class Gastropoda and two species is of Family Pisididae of the class Bivalvia. Melanoides tuberculata of family Thiaridae was most dominant species ranged from 234 org/m2 (spring) to 802 org/m2 (summer). Class Bivalvia is represented by only 2 species Pisidium mitchelli and Sphaerium indicum in which P. mitchelli was dominant and had its minimum density 72org/m2 in monsoon and maximum 360org/m2 in winters. Different biological indexes are used to determine the diversity, dominance, species richness and evenness of the observed malacofauna. The result emphasize the importance of conserving the world’s freshwater mollusks populations, which are declining at an alarming rate through habitat destruction, pollution declines in host fish and the invasion of non-native biota.